Evaluating the vocabulary of the planning and colors curriculum in the Department of Architectural Design and Decoration (Journal of the College of Basic Education, 2022)
Evaluation is the means by which the extent to which the curriculum achieves the goals set for it, the detection of positive and negative aspects in it, and the observation of aspects in which the curriculum is effective and other aspects that require modification, and since the Department of Architectural Design and Decoration at the Institute of Applied Arts is one of the institutions that aims to Preparing a middle staff specialized in designing and decorating buildings, and for the purpose of preparing a curriculum in light of the positive scientific development, and based on the above, the researcher conducted his current research, which aims to evaluate the curriculum of planning and colors in the Department of Architectural Design and Decoration.